Fokus Grup Diskusi Mitra Penta Helix dalam Evaluasi Kesiapsiagaan Kebencanaan Pasca Gempa 7,3 Skala Richter di Kelurahan Parupuk Tabing - Mahathir Mahathir; Devia Putri Lenggogeni; Gusti Sumarsih; Hema Malini; Fitra Yeni; Bunga Permata Wenny; Agus Sri Banowo (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
The Penta-helix collaboration on disaster preparedness requires a comprehensive and collaborative role between various fields in society as an initiative from the National Agency for Disaster Countermeasure by strengthening the role of academics, government, the private sector, organizations and the community itself. This activity aims to evaluate the disaster preparedness necessity of the community after the 7.3 magnitude earthquake through a focus group discussion of the disaster preparedness penta-helix collaboration team in a district of West Sumatra. This activity was carried out on May 24. This activity invited disaster nursing experts from the Polytechnic University of Hong Kong. The activity was carried out with focus group discussions inviting various essential community disaster preparedness stakeholders, namely the Faculty of Nursing Universitas Andalas, BNPB, BASARNAS, Ministry of Health, Indonesia Red Cross (PMI), and community leaders. On this occasion, thematic results were obtained from focus group discussions on the importance of community empowerment, strengthening family values and vulnerable groups’ advocacy. Through evaluating disaster preparedness planning, it is crucial to know the need to be met after the community responds to an actual disaster event. The collaborative role of disaster penta-helix stakeholders can provide recommendations for strengthening disaster preparedness planning.